2013
DOI: 10.1186/1477-7819-11-76
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study: platinum-based induction chemotherapy combined with gemcitabine or paclitaxel for stage IIB-IIIA central non-small-cell lung cancer

Abstract: BackgroundSeveral encouraging phase III clinical trials have evaluated platinum-based induction chemotherapy against stage IIB-IIIA non-small-cell lung cancer (NSCLC). Chemotherapy efficacy was assessed using common regimens in this retrospective analysis.MethodsFrom 2007 to 2011, the clinical records of stage IIB-IIIA NSCLC patients undergoing surgery after neoadjuvant chemotherapy were reviewed. Gathered data were tested for significance and variables impacting survival were assessed by univariate and Cox re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Previously, a large of studies including prospective and retrospective analyses focused on the treatment for NSCLC [8][9][10][11][12][13][14][15] , because NSCLC accounted for 85% of lung cancer cases 16 . It has been reported that surgery combined with chemotherapy/ radiotherapy may improve the survival of the patients with advanced NSCLC 9,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, a large of studies including prospective and retrospective analyses focused on the treatment for NSCLC [8][9][10][11][12][13][14][15] , because NSCLC accounted for 85% of lung cancer cases 16 . It has been reported that surgery combined with chemotherapy/ radiotherapy may improve the survival of the patients with advanced NSCLC 9,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported some risk factors related to the occurrence of BPF after lung surgery. Among them, the most reported risk factors include age at surgery (11,26), diabetes (9,11), COPD (27), neoadjuvant therapy (11)(12)(13), albumin level (8,28), as well as intraoperative factors such as residual margin (3), right pneumonectomy (8,17,18,29), and right middle and/or lower lobectomy (8,30). In this study, we used bronchoplasty patients as the study population, and obtained some of the same risk factors as those for the high incidence of BPF after pneumonectomy and lobectomy, such as residual margin and right middle and/or lower lobectomy.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies showing the efficacy of neoadjuvant therapy with platinum-based combination in patients with stage III NSCLC (10,11). However, a standard chemotherapy protocol could not be determined.…”
Section: Introductionmentioning
confidence: 99%